2019
DOI: 10.1016/j.ceramint.2018.11.225
|View full text |Cite
|
Sign up to set email alerts
|

Combination of structural and microstructural effects in the multiferroic response of Nd and Ti co-doped BiFeO3 bulk ceramics

Abstract: Different dopant strategies are currently under investigation in order to overcome the many problems that limit the commercial viability of BiFeO 3-based ceramic devices. Neodymium substitution onto the A site of the perovskite lattice provokes significant changes in the crystal structure of the parent material which can derive in enhanced multiferroic properties, but the conductivity in the bulk system is still too high. Titanium doping on the other hand generates a distinctive micro-nanostructure in the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…As described, in the bulk samples the formulated titanium ions segregate to the grain boundaries as the temperature rises, until they form a highly resistive Ti-rich interconnected skeleton that neatly reduces the conductivity of the material. 4,5 In the films, on the contrary, this titanium stays confined in the perovskite structure, no such skeleton of Ti-enriched boundaries is ever formed, and as a direct consequence the conductivity is not sufficiently restrained: at room temperature, some leakages are still present in the films, which initially hinders the exploitation of their ferroelectric potential. This impediment however disappears when the ferroelectric response of the films is measured at liquid nitrogen temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As described, in the bulk samples the formulated titanium ions segregate to the grain boundaries as the temperature rises, until they form a highly resistive Ti-rich interconnected skeleton that neatly reduces the conductivity of the material. 4,5 In the films, on the contrary, this titanium stays confined in the perovskite structure, no such skeleton of Ti-enriched boundaries is ever formed, and as a direct consequence the conductivity is not sufficiently restrained: at room temperature, some leakages are still present in the films, which initially hinders the exploitation of their ferroelectric potential. This impediment however disappears when the ferroelectric response of the films is measured at liquid nitrogen temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…3a), but in the BNFTO sample it goes together with the entrance of a new maximum around 2y = 47.51 which must be ascribed to the orthorhombic Pbam phase of BiFeO 3 . 5 This different scenario is nevertheless not surprising and relates to the specific formulation used for the two co-doped compositions. On one hand, the BSFTO sample was formulated with 12 mol% of samarium, which places this composition right on the edge of a theoretical morphotropic phase boundary (MPB); 33 this is found to render an enhancement of the electromechanical (piezoelectric) properties of the material and, actually, in the particular case of Sm-modified BiFeO 3 ceramics it has been observed that such enhancement could be quite significant in the vicinity of the MPB (i.e., with no need to be inside the MPB itself).…”
Section: Microstructural and Structural Characterization Of The Filmsmentioning
confidence: 99%
See 3 more Smart Citations